Discourses on mathematics education in the context of early assessment - Walla, Maria; Palmér, Hanna (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
This paper is about the meanings Swedish preschool class teachers ascribe to early mathematics education when talking about assessment. The assessment material is new national, mandatory assessment material for six-year-old students. Based on a discourse analysis of four focus groups, five discourses were construed: preschool class mathematics is unique; the role of preschool class mathematics is changing; to assess is to categorize; assessment contributes to equity; and individualization implies grouping by level. The results illustrate how teachers hope that the status of and equity in preschool class mathematics education will increase by means of the assessment. However, the teachers’ talk about categorizing and grouping students may have implications for equity.